The Urgency of Consumer Protection in Electronic Transactions in Online Gaming: Positive Law and Islamic Law Perspectives - Muhammad Hishnul Islam; Aditia Prastyan Supriadi; Miftahul Huda (Istinbath : Jurnal Hukum, 2025)
Electronic transactions in online games have been an issue in modern digital transactions. Consumers who purchase electronic balances, especially through third parties, often experience losses, while an effective legal protection mechanism is absent. This condition therefore creates legal uncertainty, injustice, and psychological risks for consumers. This study analyzes the urgency of consumer protection against problematic electronic transactions in online games, from both the perspective of positive law and that of the maqāṣid al-syarī‘ah. This study is categorized as normative juridical legal research, employing statutory and conceptual approaches. Primary legal materials were sourced from Law No. 8 of 1999 concerning Consumer Protection and Law No. 1 of 2024 concerning Electronic Information and Transactions, while secondary legal materials comprised literature, journals, and relevant articles. The results indicate that current regulations remain suboptimal in protecting digital consumers, particularly for intangible and cross-border transactions. From the perspective of maqāṣid al-syarī‘ah, the loss of electronic balance without clear accountability is a violation of the principles of property protection (hifẓ al-mal), protection of reason (hifẓ al-aql), and protection of life (hifẓ al-nafs). Therefore, regulatory reform to address the challenges of digital transaction development and the application of the principles of maqāṣid al-syarī‘ah is required to ensure justice, welfare, and stability for consumers.